2015
DOI: 10.1109/twc.2015.2430341
|View full text |Cite
|
Sign up to set email alerts
|

On Fundamental Trade-offs of Device-to-Device Communications in Large Wireless Networks

Abstract: This paper studies the gains, in terms of served requests, attainable through out-of-band deviceto-device (D2D) video exchanges in large cellular networks. A stochastic framework, in which users are clustered to exchange videos, is introduced, considering several aspects of this problem: the videocaching policy, user matching for exchanges, aspects regarding scheduling and transmissions. A family of admissible protocols is introduced: in each protocol the users are clustered by means of a hard-core point proce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 20 publications
(64 reference statements)
1
45
0
Order By: Relevance
“…However, only a few works have tried to figure out the caching gain of the distributed cache-enabled nodes in the stochastic geometry framework [10]- [12]. Without consideration of small scale fading, a low-complexity algorithm for finding the optimal caching probability was proposed in [10] to minimize the average caching failure probability in a D2D network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few works have tried to figure out the caching gain of the distributed cache-enabled nodes in the stochastic geometry framework [10]- [12]. Without consideration of small scale fading, a low-complexity algorithm for finding the optimal caching probability was proposed in [10] to minimize the average caching failure probability in a D2D network.…”
Section: Introductionmentioning
confidence: 99%
“…In [11], a tradeoff between the cache memory size and the density of BSs was investigated in a cache-enabled small BS network when the files are cached in order of popularity. The authors of [12] showed that a tradeoff between a global metric (i.e., the fraction of served requests in the network) and a local metric (i.e., the fraction of served requests per cluster) in a cluster-based D2D communication network, when the caching placement follows an arbitrary distribution.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, our work differs from the aforementioned works in terms of studying deployment aspects of cache-enabled small base station. Similar lines of work in terms of analysis with stochastic geometry tools can be found in [20,23]. However, the system model and performance metrics are different than what is studied here a .…”
Section: Introductionmentioning
confidence: 80%
“…More precisely, observe that E [τ 1 ] is identical to (i) of (22). Thus, following the steps from (23) to (27), we obtain: …”
Section: Proof Of Propositionmentioning
confidence: 98%
See 1 more Smart Citation